TRANSFORMASI SISTEM PENDIDIKAN INDONESIA DI ERA DIGITAL: KAJIAN KEBIJAKAN DAN IMPLIKASI SISTEMIK - Ahmad Saeful Ahyar; Muhammad Ihsan Dacholfany; Ayub Kumalla; Akbar Rahman; Darul Mustofa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Educational transformation in the digital era requires comprehensive changes in the education system, not merely the use of technological devices in learning. This article aims to analyze the transformation of the Indonesian education system in the digital era through the perspective of educational systems and policy document analysis. This study employs qualitative research based on document analysis using content analysis. The sources include literature on educational systems and five national regulations, namely Minister of Education, Culture, Research, and Technology Regulation Number 12 of 2024, Minister of Primary and Secondary Education Regulation Number 13 of 2025, Government Regulation Number 17 of 2025, Minister of Communication and Digital Affairs Regulation Number 9 of 2026, and the 2026 Joint Ministerial Decree on Guidelines for the Utilization and Learning of Digital Technology and Artificial Intelligence. The findings show that digital education transformation is a systemic change involving curriculum, learning processes, teachers, students, families, school governance, and child protection. The distinctive contribution of this article lies in mapping digital education transformation as a systemic process that integrates curriculum policy, artificial intelligence literacy, academic ethics, and child protection into a single analytical framework. This article concludes that the transformation of the Indonesian education system in the digital era requires integration among policy, educational practice, school readiness, family roles, digital literacy, academic integrity, personal data protection, and the safety of the digital ecosystem. ABSTRAK Transformasi pendidikan di era digital menuntut perubahan sistem pendidikan secara menyeluruh, bukan hanya penggunaan perangkat teknologi dalam pembelajaran. Artikel ini bertujuan menganalisis transformasi sistem pendidikan Indonesia di era digital melalui perspektif sistem pendidikan dan analisis dokumen kebijakan. Metode yang digunakan adalah penelitian kualitatif berbasis studi dokumen dengan teknik analisis isi. Sumber kajian meliputi literatur tentang sistem pendidikan serta lima regulasi nasional, yaitu Permendikbudristek Nomor 12 Tahun 2024, Permendikdasmen Nomor 13 Tahun 2025, PP Nomor 17 Tahun 2025, Permenkomdigi Nomor 9 Tahun 2026, dan SKB Pedoman Pemanfaatan dan Pembelajaran Teknologi Digital dan Kecerdasan Artifisial Tahun 2026. Hasil kajian menunjukkan bahwa transformasi pendidikan digital merupakan perubahan sistemik yang melibatkan kurikulum, pembelajaran, guru, peserta didik, keluarga, tata kelola satuan pendidikan, dan pelindungan anak. Kontribusi khas artikel ini terletak pada pemetaan transformasi pendidikan digital sebagai proses sistemik yang mempertemukan kebijakan kurikulum, literasi kecerdasan artifisial, etika akademik, dan pelindungan anak dalam satu kerangka analisis. Artikel ini menyimpulkan bahwa transformasi sistem pendidikan Indonesia di era digital memerlukan keterpaduan antara kebijakan, praksis pendidikan, kesiapan satuan pendidikan, peran keluarga, literasi digital, integritas akademik, pelindungan data pribadi, dan keamanan ekosistem digital.